2002
DOI: 10.1111/j.1752-1688.2002.tb04370.x
|View full text |Cite
|
Sign up to set email alerts
|

AN EVALUATION OF PHYSICAL STREAM HABITAT ATTRIBUTES USED TO MONITOR STREAMS1

Abstract: The last few decades have seen an increased reliance on the use of stream attributes to monitor stream conditions. The use of stream attributes has been criticized because of variation in how observers evaluate them, inconsistent protocol application, lack of consistent training, and the difficulty in using them to detect change caused by management activity. In this paper, we evaluate the effect of environmental heterogeneity and observer variation on the use of physical stream attributes as monitoring tools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 38 publications
0
88
1
Order By: Relevance
“…A wide range of methods are available and provide a tangible resource for decision making, management and restoration plans (Johnson et al 2001, Roper et al 2002. The Bank Erosion Hazard Index (BEHI) and near-bank stress (NBS), developed by Rosgen (1996Rosgen ( , 2001) are some of the most common methods used (Somervielle & Pruitt 2004).…”
Section: Sanitary Surveysmentioning
confidence: 99%
“…A wide range of methods are available and provide a tangible resource for decision making, management and restoration plans (Johnson et al 2001, Roper et al 2002. The Bank Erosion Hazard Index (BEHI) and near-bank stress (NBS), developed by Rosgen (1996Rosgen ( , 2001) are some of the most common methods used (Somervielle & Pruitt 2004).…”
Section: Sanitary Surveysmentioning
confidence: 99%
“…These authors concluded that alternative methods need to be developed to adequately describe stream substrate and reduce the level of variation due to streams and observers. Rather that simply imply that stream substrate measures are impractical (Roper et al 2002(Roper et al : p. 1644), these authors should have discussed the obvious biases introduced in their sampling methodology as described by Bunte and Abt (2001b), whom they cite. Burton (2000) used a 100-intersection grid to follow trends in fine sediment (<6.4 mm) in streams on the Boise National Forest, but did not specify grid spacing.…”
Section: Grid Methodsmentioning
confidence: 99%
“…This grid method (Roper et al 2002, Archer et al 2004) relied on only three random tosses of a grid frame within a pool tailout. Even though the toss was reportedly random, three tosses are not sufficient to ensure representation of the entire channel cross-section, given its potential spatial heterogeneity.…”
Section: Grid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional stream classification methods, however, suffer from several fundamental limitations (Poole et al 1997, Goodwin 1999, Roper et al 2002. Typical approaches include process-oriented categorizations (Whiting andBradley 1993, Montgomery andBuffington 1997), visual qualitative schemes (Bisson et al hydrodynamic simulations, remotely sensed data, and fuzzy classification techniques to explore potential alternative representations of in-stream habitat and characterize spatial patterns of classification uncertainty.…”
Section: Introductionmentioning
confidence: 99%